MEMBANGUN EKONOMI PEDESAAN DENGAN FINANCIAL INCLUSION MELALUI LEMBAGA KEUANGAN SHARIAH - Fauzia, Ika Yunia (An-Nisbah: Jurnal Ekonomi Syariah, 2015)
Financial inclusion is expected to create programs that can make people prosperous society through empowerment. As has been done by the Grameen Bank with the concept of womenâs empowerment, GTZ (Germany) and IFC. Financial inclusion is a true essence of Islamic economy, by strengthening qard hasan for developing the rural sector and empower the community. Funds can be taken from ZISWAF, especially endowments which has enormous potential to build the country. There are several challenges and obstacles in the implementation of fnancial inclusion by Islamic fnancial institutions, among which are human resources, infrastructure and funding. More than the other problems is the lack of good coordination among the scholars in the countryside and the Economist Sharia associated program to unify perceptions of Islamic fnancial institutions in general and in particular fnancial inclusion.Keywords: Financial inclusion, empowerment, Islamic fnancial institutions